2013
DOI: 10.1038/ja.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

Intervenolin, a new antitumor compound with anti-Helicobacter pylori activity, from Nocardia sp. ML96-86F2

Abstract: Because stromal cells can regulate the growth and metastasis of tumor cells, a compound that modulates the interaction between the stromal cells and the tumor cells can control the tumor progression. In the course of our screening for such a compound, we have isolated a new compound, intervenolin, from the culture broth of Nocardia sp. ML96-86F2. Intervenolin inhibits the growth of human gastric and colorectal cancer cell lines in the coculture with the respective organ-derived stromal cells more strongly than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
0
28
0
1
Order By: Relevance
“…While fewer studies were carried out on isolation and purification of chemical constituents from other several genera, including Nocardia, Gordonia, and Tsukamurella (Fu et al, 2011;Kawada et al, 2013;Kobayashi et al, 1997;Sugiyama et al, 2015). In this study, 24 compounds were obtained from Williamsia sp.…”
Section: Chemotaxonomic Significancementioning
confidence: 98%
“…While fewer studies were carried out on isolation and purification of chemical constituents from other several genera, including Nocardia, Gordonia, and Tsukamurella (Fu et al, 2011;Kawada et al, 2013;Kobayashi et al, 1997;Sugiyama et al, 2015). In this study, 24 compounds were obtained from Williamsia sp.…”
Section: Chemotaxonomic Significancementioning
confidence: 98%
“…ITV inhibits the growth of several human cancer cell lines. 11 ITV and its derivatives also exhibit anti-H. pylori activity in vitro. 12,13 Here, we demonstrated that the ITV derivative, AS-1934, showed anti-H. pylori activity including antibiotic-resistant strains in vitro and exerted anti-H. pylori activity in vivo.…”
Section: Introductionmentioning
confidence: 95%
“…The minimum inhibitory concentrations (MICs, μg/ml) against H. pylori were determined by the micro broth dilution method in 96-well plates as described previously. 11 MICs for aerobic bacteria were determined by the agar dilution streak method recommended by Clinical and Laboratory Standards Institute document M07-A7. 40…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…In a recent study, we found a novel compound, intervenolin (ITV), from the culture medium of Nocardia sp. Ml96-86F2 (11). ITV inhibited the in vitro growth of human gastric cancer cells.…”
Section: Introductionmentioning
confidence: 98%